Synthesis,characterisation and antibacterial,antifungal activities of schiff bases of 4 - (2- aminphenyl)morpholines. - GNANA RUBA PRIYA.M,; PANNEERSELVAM.P,; KARIKALAN .M, (International Journal of Pharma and Bio Sciences, 2011)
A Series of Schiff’s bases of 4(2-amino phenyl) morpholines (1-V) were synthesized compounds were confirmed by IR, 1HNMR and MASS spectrum. All the newly synthesized compounds have been screened for their in vitro antibacterial activities against S.aureus , S. epidermis, B. cereus, B. subtilis, Ps. aureus, Kl. pneumonia and E. coli and antifungal activities against A. niger and C. albicans. Their minimal inhibitory concentration (MIC) values ranged between 1-10 µg/ml. The screening data indicates that the compounds I to V have promising anti-bacterial activity and antifungal activity by disc diffusion method by measuring the zone of inhibition and the results were compared to standard drugs ciprofloxacin and ketoconazole respectively.